Neutropenic Diet Cannot Reduce the Risk of Infection and Mortality in Oncology Patients With Neutropenia - Ma, Yimei; Lu, Xiaoxi; Liu, Hanmin (Frontiers in Oncology, 2022)
Background: The purpose of the systematic review and meta-analysis is to evaluate the effect neutropenic diet and control diet on infection and mortality rates in oncology patients with neutropenia. Methods: We searched the following the following English electronic databases: PubMed, Embase, Cochrane Central Register of Controlled Trials, and Google Scholar Engine. The published studies involving the neutropenic diet (Study group) and control diet (Control group) in oncology patients with neutropenia were searched. The focus of the meta-analysis was on the outcomes of infection and mortality rates. A subgroup analysis was also performed. Results: A total of 6 studies were included, with a total sample size of 2589 patients. The patients in the study group had similar the infection rate compared with the patients in the control group (P = 0.11). The patients in the study group had similar the mortality rate compared with the patients in the control group (P = 0.74). Another subgroup analysis that the incidence of infection was also similar for the pediatric (P = 0.74) and adult (P = 0.11) oncology patients between the study and control groups. Conclusions: Based on the current evidence, this meta-analysis showed that the application of a neutropenic diet cannot reduce the risk of infection and mortality in oncology patients with neutropenia. However, more rigorous randomized controlled trials are needed to confirm the conclusion in future.